WEB-BASED ACCESS AND ATTENDANCE SYSTEM FOR ELECTRICAL ENGINEERING STUDENTS AT UMK USING BARCODE ON STUDENT ID CARDS (KTM) - Rifqi Zulhilmi; Noor Yulita Dwi Setyaningsih; Mohammad Iqbal (Jurnal Media Elektrik, 2025)
This research aims to develop a Web-Based Attendance and Access System for Electrical Engineering Students at Muria Kudus University (UMK) using Student Identity Cards (KTM) equipped with barcode technology. This system not only manages student attendance digitally but also improves classroom security by integrating a barcode verification-based electromagnetic locking system. The development process of this system uses the Research and Development (R&D) method with the ADDIE model which consists of the stages of analysis, design, development, implementation, and evaluation. In software testing, login tests are carried out, barcode system integration tests with databases, and data processing speed and system resilience tests. The results of the system test showed that the system performed well under varied network conditions, although there was a dependence on network quality that affected the system response time. In addition, barcode scanning distance testing showed that the GM66 barcode reader has an optimal range between 5 cm to 30 cm. System testing also includes a resiliency test to unstable network conditions, where the system can handle connection loss by performing temporary storage and data synchronization after the connection is restored. Overall, the test results show that this system is reliable in managing classroom attendance and security and has the potential to be applied more widely in the campus environment. This research makes an important contribution in improving the efficiency of academic administration and strengthening the campus security system.